Plants, biotechnology and agriculture - Murphy, Denis J (CABI, 2011)
At a time when the world's food supplies are increasingly unable to meet the needs of a burgeoning population, there is significant diversity of opinion concerning the benefits and perceived dangers of the application of biotechnology to food production. This book provides the reader with a guide to plants as both organisms and resources.